(untitled) (American Journal of Islam and Society, 2013)
On May 17, 2013, Joseph V. Montville, director of the Esalen Institute’s “Toward the Abrahamic Family Reunion” project (http://abrahamicfamilyreunion. org), addressed a select audience at the IIIT headquarters on pre-Zionist Jewish scholarly interest in Islam. He began by recalling how German and Austro-Hungarian Jewish scholars discovered remarkable similarities in the Torah, the Talmud, and the Qur’an. While hardly a surprise to Muslims, this was a “major revelation and surprise” to European Christian philologists and historians of religions. This new interest emerged as Europe was losing its fear of the Ottoman Empire, and of Muslims in general, because the now militarily inferior empire was in retreat and anti-Semitism was on the rise. Jewish intellectuals sought to blunt this latter trend by combating Christian disdain, if not hostility, of Jews and Judaism. They therefore played a major role in this scholarship, for, quoting from Bernard Lewis [“The State of Middle Eastern Studies,” American Scholar 48, no. 3 (summer 1979: 369-70)]: ...